Common Mistakes in Pronunciation among Students in The English for Specific Purposes Department, Hanoi University - Ta Thi Thanh Hien, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
When learning English as a second language in a nation with a wide variety of races and cultures, the influence of the native tongue is nearly inevitable. Both the performance and communicative competence of learners can be negatively impacted by this influence. This paper is written for students in the English for Specific Purposes Department (ESPD), Hanoi University, who want to improve their learning of English Pronunciation. This mixed-methods study combine quantitative and qualitative methodologies. It focuses on some common pronunciation errors that EPSD students made when speaking English by analysing 120 recordings for the students’ mid-term test from their second semester in the academic year 2023-2024. Some common pronunciation errors are found, including consonant endings and vowel sounds. The study also shares some strategies for learners to improve their English pronunciation. It will be a helpful reference source for not only lecturers and learners at ESPD, Hanoi University, but other educational institutions across Vietnam.Received 5th July 2024; Revised 5th August 2024; Accepted 7th September 2024